COVID-19 related risk perception and altruistic response amongst undergraduates on reopening of educational institutes - Bushra Rabbani; Faisal Ahmed; Ammarah Saeed; Syed Muhammad Zulfiqar Hyder Naqvi; Mariam Tariq; Mehrunnisa Umar (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the coronavirus disease-2019-related risk perception and altruistic response among undergraduate medical students post-lockdown. Method: The analytical cross-sectional study was conducted from October 1, 2020, to March 31, 2021, at the Baqai Medical University, Karachi, and comprised undergraduates aged 16 and above, studying in medical, dental, physiotherapy, pharmacy and Information technology departments. Data was collected using a structured and standardised online questionnaire. Positive responses led to a perceived risk score ranging 0-9, with a higher score indicating a greater perception of risk. The score was corelated with demographic variables. Data was analysed using SPSS 21. Results: Of the 743 subjects, 472(63.5%) were females. The overall mean age of the sample was 21.34±1.8 years. The mean risk perception score was 3.8±2.5, and it was significantly associated with disease exposure (p<0.001). Altruism had a strong association with the perceived risk score (p<0.001), indicating lower risk perception. Conclusion: The risk perception among the students was low, pointing towards a need of psychological assistance program for the students. Key Words: COVID-19, Risk, Perception, Students, Academics, Institutes.